PERDARAHAN SUBARACHNOID - Asrizal Asril; Reno Sari Caniago (Yayasan Nusantara Hasana Berdikari, 2026)
Subarachnoid hemorrhage (SAH) is a neurological emergency characterized by bleeding into the subarachnoid space, most commonly caused by rupture of an intracranial aneurysm. This condition is associated with high morbidity and mortality rates and requires prompt diagnosis and management. Patients typically present with sudden severe headache, often described as “the worst headache of life,” accompanied by nausea, vomiting, decreased level of consciousness, neck stiffness, and focal neurological deficits. Diagnosis is established through clinical evaluation supported by neuroimaging, particularly non-contrast computed tomography (CT) scan, and may be followed by lumbar puncture or cerebral angiography if necessary. Early treatment focuses on stabilizing the patient, preventing rebleeding, managing intracranial pressure, and addressing complications such as vasospasm and hydrocephalus. Definitive management may involve surgical clipping or endovascular coiling of the aneurysm. Comprehensive and timely intervention is essential to improve patient outcomes and reduce the risk of long-term neurological disability.